Construction Time of Three Wall Types Made of Locally Sourced Materials: A Comparative Study - Wojciech Drozd; Agnieszka Leśniak; Sebastian Zaworski (Advances in Materials Science and Engineering)
Similarly to any other industry, the construction sector puts emphasis on innovativeness, unconventional thinking, and alternative ideas. At present, when sustainable development, ecology, and awareness of people’s impact on the environment grow in importance, low impact buildings can become an innovative alternative construction technology for the highly industrialized construction sector. The paper presents a comparative study of three walls made of available materials used locally, which can be classified as biosourced materials, in terms of construction time. The comparison of times necessary to make 1 m2 of the wall allows us to decide which building technology is more advantageous in terms of the construction duration. A shorter construction time means lower labour costs and lower expenses for construction machines. In order to obtain answers to the questions posed, the authors made extensive searches of source data on the time-consuming building works which used locally sourced materials. Reference is made to “Temporary principles of erecting clay buildings” issued by the Institute of Housing Construction in Warsaw (Poland). Three types of walls made of locally sourced materials were studied: a wall made of clay blocks insulated with mineral wool boards, a wall made of clay compacted in formwork, and one insulated with mineral wool boards and wooden frame structure filled with straw bales and cladded with fibreboards. The layers have been chosen in such a manner that heat transfer coefficient values for the studied variants are as equal as possible (0.2 W/m2 K), thus allowing a reliable comparative study.